Literature Review: Efektivitas, Keamanan, dan Biaya Terapi Imidafenacin untuk Pasien Overactive Bladder - Halim, Steven Victoria (Politeknik Kesehatan Tanjung Karang, 2020)
Imidafenacin is a new antimuscarinic agent in Indonesia that was recently approved in 2019 to treat overactive bladder (OAB) symptoms, including urinary incontinence, urinary frequency, and urinary urgency. As a new OAB medication in the Indonesian commercial market, a comprehensive review on the efficacy, safety, and cost of imidafenacin are essentially needed to optimize the responsible use of this drug, particularly in the era of universal coverage implementation in Indonesia. This review aimed to describe the profile of imidafenacin and to compare the efficacy, safety, and cost of imidafenacin with the other antimuscarinic drugs in Indonesia, and the guideline recommendations towards when to use imidafenacin for OAB treatment. Only results from systematic reviews and meta-analyses were used in the efficacy and safety comparison. Our review found that the efficacy of imidafenacin was relatively comparable to the other antimuscarinic drugs in Indonesia, including solifenacin, tolterodine, dan propiverine. Also, a better safety profile was found in the imidafenacin group, in particular, imidafenacin caused less dry mouth and constipation. This could be attributable to the higher affinity of imidafenacin to the M3 receptor resulting in less antimuscarinic effect at the other receptors. From the cost perspective, the cost of medication by using imidafenacin was relatively lower compared to the other antimuscarinic drugs in Indonesia. It, therefore, could be suggested to use imidafenacin as a potential agent for OAB.